The hybrid nature of the soviet rituals of the 1920’s: Church traditions - Tabunshchikova, Lyudmila Viktorovna (Opción, 2019)
This article explores the periodicals of the 1920s, as well as the methodological literature of the Soviet era on the organization of new rituals, which enabled the author to trace the struggle of the government with the Church. In result, in the 1920s, there were three points of view on the role of state in the development of new non-religious rites: no state regulation, no regulation with strong state focus, and active state administration, development and subsequent introduction of new rituals by the state. In conclusion, civil ritualism was created in Soviet Russia during the anti-religious campaign of the 1920s